A Qualitative Assessment of Guinea-Bissau’s Hunting History and Culture - and Their Implications for Primate Conservation - Silva, Maria J. Ferreira da (2021)
Illegal hunting and trade threaten the high biodiversity of Guinea-Bissau (GB) in West Africa, particularly for nonhuman primates (NHP). Primate carcasses are sold at bushmeat markets and at restaurants and the primate pet trade is active. Traditional medicine practitioners also use NHP body-parts further promoting the commerce of NHP skins. A better understanding of hunting and related trade activities, including the profile of hunters and their motivations, would improve NHP conservation in GB. However, information on commercial hunting is incomplete due to a general unwillingness to describe illegal activities by the local communities. Here, we investigated aspects of hunting practice and related commercial activities targeting NHP in GB by collecting qualitative ethnographic information using semi-structured interviews. Participants were asked about hunted species, techniques and hunting locations, their motivations to hunt wild NHP, uses of carcasses, and their perceptions on the demographic trajectory of hunted species. Eight participants in the study listed species hunted in GB, which included a total of seven NHP. Hunting areas described were spread across southern GB and included locations within the limits of national protected areas and formalized ecological corridors. Participants mentioned the trade in NHP meat at bushmeat restaurants as the primary motivation for primate-targeted hunting, with the exception of western chimpanzees, which are specifically targeted for the exotic pet trade. Several strategies are used in hunting NHP, including traps, firearms, and hunting dogs. The majority of hunted NHP were perceived as having declined in population size during recent decades. Episodes when military groups hunted NHP intensively using more sophisticated weapons and methods in the 1980s were also described. This study highlights how hunting and related activities are complex and multi-dimensional and illustrates the use of ethnographic methods to improve knowledge about illegal and concealed practices impacting NHP conservation. Our results suggest an urgent need to raise awareness of local communities and subsistence hunters living within protected areas about the environmental and social impacts of hunting.